In vitro fermentation of diets containing sweet potato flour as a substitute for corn in diets for ruminants - Demarco,Claudia Faccio (2020)
ABSTRACT: With the intensification of production systems, dairy cow feeding has undergone changes creating the need to increase substitute feed options, focusing on more efficient, modern, and sustainable alternatives. Few researches were carried out evaluating the inclusion of sweet potato flour as an energy source in substitution of maize for ruminants. The aim of this study was to evaluate the in vitro gas production of ground corn replacement by sweet potato flour at different levels. For in vitro gas production, four treatments were performed, consisting of corn replacement by sweet potato flour at the levels of 0, 33, 66, and 100%, in a diet consisting of corn silage, soybean meal, and ground corn. In vitro incubations were conducted in sealed bottles containing 50 ml of the inoculum prepared using ruminal fluid and 0.5 g of each treatment. Gas production was determined in 96 consecutive hours. The cumulative gas production was greater when the corn was 100% replaced by SPF (224 ± 1.45 and 231.9 ± 1.45 ml/g DMi for 0 and 100% of replacement, P = 0.01). Degradation rates were 7.10, 7.59, 8.08, and 8.59 ± 0.06% per hour for the 0, 33, 66, and 100% replacement rates, respectively (P<0.001). There was also a difference (P = 0.002) in the lag time, in which diets with the highest SPF inclusion had a lower colonization time. In conclusion, sweet potato flour produced more gas and was more rapidly degraded than corn.